Evaluation of disaster management and preparedness of a petrochemical in Malaysia - Chew, Soong Kong (2000)
In tandem with the intensification of the country's industrialization programs, the petrochemical industry was identified as one of the sectors that have tremendous potential for growth. Malaysia is now entering into a new era in the development of its Petrochemical Industry where the path forward is to plan and implement petrochemical projects on an integrated basis to maximize on the synergy. As Integrated Petrochemical Complexes (IPCs) is one of the most hazardous operation to be undertaken in the country, there is a need to effectively mitigate against a whole range of incidents from emergency to crisis. This is to prevent loss of life, damage to the environment and minimize losses to property. Since prevention is always the first defense against any incident, the operators at the IPCs should at all times be equipped and prepared to response professionally to all incidents. Thus the purpose of this project is to evaluate the status of compliance by the operators in accordance to the mandated guidelines, the level of emergency preparedness of the plant's emergency response team in handling incipient stage incident, and the capability of the Complex Fire Brigade to mitigate them when it is beyond the ability of the mentioned team. The findings showed that the emergency management system is in place at both the operator and complex fire brigade level whereby it met the requirements with an overall scores of 3.19 and 3.36 respectively. Nevertheless, additional commitment is needed to enhance the level of emergency preparedness of the plant's emergency response team in handling incipient stage incident since the overall score achieved was 2.36. These finding will be highlighted to the operator for their continuous improvement, used as a benchmark for other similar plants and acts as indicators of the industry's health.